Fieldwork of the Canadian Institute in Greece in 2017 - Rupp, David W.; Carter, Tristan; Athanasoulis, Dimitris; Charami, Alexandra; Burke, Brendan; Burns, Bryan; Papadimitriou, Alcestis; Perreault, Jacques Y.; al, et (Mouseion: Journal of the Classical Association of Canada, 2020)

Fieldwork of the Canadian Institute in Greece in 2016 - Rupp, David W.; Bonias, Zizis; Perreault, Jacques Y.; Charami, Alexandra; Burke, Brendan; Burns, Bryan; Carter, Tristan; Athanasoulis, Dimitris; Nakassis, Dimitri; Gallimore, Scott; James, Sarah; Karapanou, Sophia; et al. (Mouseion: Journal of the Classical Association of Canada, 2019)
The archaeological fieldwork conducted in Greece in 2016 under the aegis of the Canadian Institute in Greece is summarized here based on the presentation given by the Director at the Institute's annual Open Meeting in Athens, in May, 2017.

Fieldwork of the Canadian Institute in Greece in 2015 - Rupp, David W.; Bonias, Zizis; Perreault, Jacques Y.; Charami, Alexandra; Burke, Brendan; Burns, Bryan; Carter, Tristan; Athanasoulis, Dimitris; Nakassis, Dimitri; Gallimore, Scott; James, Sarah; Karapanou, Sophia; et al. (Mouseion: Journal of the Classical Association of Canada, 2018)
The archaeological fieldwork conducted in Greece in 2015 under the aegis of the Canadian Institute in Greece (CIG) is summarized based on the presentation given by the director at the institute's annual Open Meeting in Athens in May 2016.

Fieldwork of the Canadian Institute in Greece in 2018 - Burke, Brendan; Athanasoulis, Dimitris; Bonias, Zisis; Burns, Bryan; Carter, Tristan; Charami, Alexandra; Gallimore, Scott; Haagsma, Margriet J.; James, Sarah; Karapanou, Sophia; Nakassis, Dimitri; Papadimitriou, Alcestis; et al. (Mouseion: Journal of the Classical Association of Canada, 2021)
The archaeological fieldwork conducted in Greece in 2018 under the aegis of the Canadian Institute in Greece (CIG) is summarized based on the presentation given by the director at the Institute’s annual Open Meeting in Athens in May 2019.